The Design and Performance of the ZEUS Central Tracking Detector z-by-Timing System - Bailey, D; Carter, R; Foster, B; Harnew, N; Heath, G; Jeffs, MD; Khatri, T; Lancaster, M; Lane, J; McArthur, I; McFall, J; Milborrow, R; et al. (1997)
The ZEUS Central Tracking Detector utilizes a time difference measurement to provide a fast determination of the z-coordinate of each hit. The z-by-timing measurement is achieved by using a Time-to-Amplitude Converter which has an intrinsic timing resolution of 36 ps, has pipelined readout, and has a multihit capability of 48 ns. In order to maintain the required sub-nanosecond timing accuracy, the technique incorporates an automated self-calibration system. The readout of the z-by-timing data utilizes a fully customized timing control system which runs synchronously with the HERA beam-crossing clock, and a data acquisition system implemented on a network of Transputers. Three dimensional space-points provided by the z-by-timing system are used as input to all three levels of the ZEUS trigger and for offline track reconstruction. The average z-resolution is determined to be 4.4 cm for multi-track events from positron-proton collisions in the ZEUS detector.